Characterization of Transcription Factor Gene OsDRAP1 Conferring Drought Tolerance in Rice - Huang, Liyu; Wang, Yinxiao; Wang, Wensheng; Zhao, Xiuqin; Qin, Qiao; Sun, Fan; Hu, Fengyi; Zhao, Yan; Li, Zichao; Fu, Binying; Li, Zhikang (Frontiers in Plant Science, 2018)
The dehydration responsive element binding (DREBs) genes are important transcription factors which play a crucial role in plant abiotic stress tolerances. In this study, we functionally characterized a DREB2-like gene, OsDRAP1 conferring drought tolerance (DT) in rice. OsDRAP1, containing many cis-elements in its promoter region, was expressed in all organs (mainly expressed in vascular tissues) of rice, and induced by a variety of environmental stresses and plant hormones. Overexpressing OsDRAP1 transgenic plants exhibited significantly improved DT; while OsDRAP1 RNA interfering plants exhibited significantly reduced DT which also accompanied with significant negative effects on development and yield. Overexpression of OsDRAP1 has a positive impact on maintaining water balance, redox homeostasis and vascular development in transgenic rice plants under drought stress. OsDRAP1 interacted with many genes/proteins and could activate many downstream DT related genes, including important transcription factors such as OsCBSX3 to response drought stress, indicating the OsDRAP1-mediated pathways for DT involve complex genes networks. All these results provide a basis for further complete understanding of the OsDRAP1 mediated gene networks and their related phenotypic effects.